Changes in dry montane shrubland cover in the Chota Valley (Imbabura and Carchi, Ecuador) between 1990 and 2020 - Vilema-Ramos, Bryan (2023)
Land use change is one of the main drivers of global change, as well as a cause of biodiversity loss. In northern Ecuador, the montane dry scrub is a characteristic ecosystem of the inter-Andean valleys and is threatened by anthropogenic intervention. This study examined the change in montane dry scrub coverage in the Chota River Valley over a 30-year period and evaluated its conservation status. The supervised classification method was applied to LANDSAT satellite images from 1990, 2007, and 2020 to analyze the rates of coverage variation. The conservation status was determined using an evaluation matrix that considered seven variables and 25 indicators and the overlap of thematic layers with GIS. The results showed a loss of 20% of montane dry scrub coverage, at an annual average of 231.83 ha/year (-0.75%) due to anthropogenic causes. These causes were responsible for the coverage change of more than half of the 8.34% of the area it occupied, mainly the expansion of the agricultural frontier with 3.96%. The pressure and effect of the identified anthropogenic factors caused the current conservation status to be Regular. Three conservation strategies are proposed: good agroecological practices, comprehensive environmental management, and environmental education.